Pengaruh Pemberian Kompos Rumput Naga (Potamogeton sp) Terhadap Pertumbuhan dan Hasil Tanaman sawui (Brassica juncea L) - Helmi Helmi; Jumar Jumar; Noor Khamidah (Universitas Lambung Mangkurat, 2022)
The mustard plant (Brassica juncea L) has green leaves and is round and oval in shape. Leaves have pinnate and branched bones. The problems are often found by farmers are lack of yields, less weight, especially on ultisol soil types. One way to increase the growth and yield of musta greens is by fertilizing. The technology used is potamogeton as organic fertilizer to fertilize the soil, increase plant growth and production, and reduce the amount of potamogeton water weed waste. Dragon grass plant is an aquatic plant belonging to the order Helobiae which becomes waste in right cascade irrigation waters which causes irrigation canals to be obstructed, cleaning of potamogeton is carried out at a certain time in which the potamogeton waste is disposed of without further. In this study, the use of potamogeton waste into compost for mustard plants aimed to determine the effect of giving potamogeton compost to mustard plants and to determine the dose of dragon potamogeton application on the growth and yield of mustard plants., leaf number, leaf width and wet weight on mustard plants because the nutrient requirement for N in potamogeton compost was not sufficient for mustard plants and an effective dose of rpotamogeton compost was not obtained.